2004
DOI: 10.1002/hup.560
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid cannabis use and panic disorder: short term and long term follow‐up study

Abstract: Acute cannabis use can be associated with the onset of panic attacks and panic disorder, and panic disorder which develops after cannabis use is responsive to pharmacotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 26 publications
(29 reference statements)
2
38
0
3
Order By: Relevance
“…THC, under certain conditions and at certain doses, exerts anxiolytic, antidepressant, and hypnotic effects in patients suffering from pain associated with cancer or multiple sclerosis and improves mood and general well-being in normal subjects (Regelson et al, 1976;Glass et al, 1980;Ashton et al, 1981;Fabre and McLendon, 1981;Ilaria et al, 1981;Martyn et al, 1995;Ashton, 1999;Wade et al, 2003). However, under different conditions and at higher doses, cannabis or THC can produce dysphoric reactions, anxiety, panic paranoia, and psychosis (Spencer, 1971;Halikas et al, 1972;Chopra and Smith, 1974;Ashton et al, 1981Ashton et al, , 2005 Dannon et al, 2004;D'Souza et al, 2004;reviewed in Hollister, 1986;Hall and Solowij, 1998).…”
mentioning
confidence: 99%
“…THC, under certain conditions and at certain doses, exerts anxiolytic, antidepressant, and hypnotic effects in patients suffering from pain associated with cancer or multiple sclerosis and improves mood and general well-being in normal subjects (Regelson et al, 1976;Glass et al, 1980;Ashton et al, 1981;Fabre and McLendon, 1981;Ilaria et al, 1981;Martyn et al, 1995;Ashton, 1999;Wade et al, 2003). However, under different conditions and at higher doses, cannabis or THC can produce dysphoric reactions, anxiety, panic paranoia, and psychosis (Spencer, 1971;Halikas et al, 1972;Chopra and Smith, 1974;Ashton et al, 1981Ashton et al, , 2005 Dannon et al, 2004;D'Souza et al, 2004;reviewed in Hollister, 1986;Hall and Solowij, 1998).…”
mentioning
confidence: 99%
“…Some of the cannabinoid receptor agonists produce anxiolytic effects in the plus maze at low doses (35) and produce an anxiogenic profile in higher doses (41). Furthermore, it has been shown that THC and other CB1 receptor agonists exert a bidirectional influence on anxiety responses according to the administrated dosage (42)(43)(44)(45)(46)(47). The biphasic effects of cannabinoids on anxiety-related responses have been extensively documented in rodents.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, high concentrations of the same compounds are generally associated with the opposite outcomes (31, 49,50). In human studies, it has been reported that consumption of modest amounts of cannabis and CB1 receptor agonists would result in euphoria, relaxation, heightened perception, sociability, and creativity while moderate to high doses have been reported to elicit phobia, agitation, panic, dysphoria, and cognitive impairments (42)(43)(44)(45)(46)(47). In line with these premises, early studies showed a robust anxiolytic effect of lowdose nabilone in comparison with placebo (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…According to various studies, increasing cannabis use is associated with increasing levels of depression [19,20]. Moreover cannabis use has also been correlated to depressive disorders [31] anxiety symptoms [6,25,32,33] and anxiety vulnerability [34,35].…”
Section: Methodsmentioning
confidence: 99%